2013
DOI: 10.1007/s00404-013-2894-9
|View full text |Cite
|
Sign up to set email alerts
|

An approach to evaluate the efficacy of vaginal misoprostol administered for a rapid management of first trimester spontaneous onset incomplete abortion, in comparison to surgical curettage

Abstract: Misoprostol could be a safe and easily accessible alternative to surgical evacuation, in cases of first trimester spontaneous onset incomplete miscarriage, and could be administered by the patient herself at home.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 16 publications
1
3
0
Order By: Relevance
“…Our findings revealed that women considered misoprostol to be effective as it was successful in evacuating the uterus. These findings are similar to what most studies have portrayed [ 15 17 , 19 22 , 35 , 36 ]. Very high levels of effectiveness of above 90% have been reported in most studies with a few showing a slightly reduced level of effectiveness (80–89%).…”
Section: Discussionsupporting
confidence: 91%
“…Our findings revealed that women considered misoprostol to be effective as it was successful in evacuating the uterus. These findings are similar to what most studies have portrayed [ 15 17 , 19 22 , 35 , 36 ]. Very high levels of effectiveness of above 90% have been reported in most studies with a few showing a slightly reduced level of effectiveness (80–89%).…”
Section: Discussionsupporting
confidence: 91%
“…A total of 114 RCTs were included in the review . The PRISMA flow chart in Figure S1 shows study selection.…”
Section: Resultsmentioning
confidence: 99%
“…In 2010 indications for abortions in Finland were social in 92%, medical in 0.5% and fetal defect-related in 3% of the cases. Other indications comprised 5% of the cases, including indications such as mother's age (under 17 or over 40 years) [15]. Surgical evacuation-dilatation has for decades been the standard treatment of early pregnancy termination.…”
Section: Discussionmentioning
confidence: 99%
“…All patients were primarily offered the medical procedure [15] [16]. Medical abortion is standard procedure in our clinic and it is primarily offered of all patients including women less than 63 days of gestation.…”
Section: Methodsmentioning
confidence: 99%